2016 XXII International Conference on Electrical Machines (ICEM) 2016
DOI: 10.1109/icelmach.2016.7732868
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and comparison of linear transverse flux and flux switching machines

Abstract: This paper investigates the design of alternative permanent magnet linear machines for use as the generator in a free piston engine. All of the machines are of a modulated pole structure with three dimensional flux flows. In transverse flux machines such as these, the current flows in a different plane to the flux path, eliminating the usual conflict between electric and magnetic loading. For a linear machine, the mass of magnets used is sensitive to whether the magnets are mounted on the stator or translator.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The initial machine topology based on previous studies [9] is shown in Fig. 1, where the translator has axially magnetised permanent magnets separated by iron pole pieces, the stator consists of three separate phases, each with a set of iron teeth surrounding the copper coil.…”
Section: Initial Machine Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…The initial machine topology based on previous studies [9] is shown in Fig. 1, where the translator has axially magnetised permanent magnets separated by iron pole pieces, the stator consists of three separate phases, each with a set of iron teeth surrounding the copper coil.…”
Section: Initial Machine Topologymentioning
confidence: 99%
“…In previous studies [7–9], linear TFMs have been compared with more conventional longitudinal topologies for use with a free‐piston engine. Simulation results show that a modulated pole machine (MPM)‐type TFM topology can achieve high force, low copper loss, and competitive power factor even under conditions of high electric loading.…”
Section: Introductionmentioning
confidence: 99%
“…The flux leakage analysis of the TFPMLEMs pointed out that reduction of the armature flux leakage can increase the power factor, and different stator topologies are investigated [16,30]. During the design process, a three dimensional (3D) finite element analysis (FEA) is necessary due to the complex geometry and fully 3D flux path [31]. The mover of FSPMLEM is made of slotted iron, the stator consists of PMs and transverse windings for each phase, as shown in Figure 4 [31].…”
Section: Different Flux Type Permanent Magnet Lemsmentioning
confidence: 99%
“…As a result, FSPMLEMs have superior reliability due to their simple and rugged mover structure, and they are featured with high force density, high efficiency but high force ripple [32,33]. The mover of FSPMLEM is made of slotted iron, the stator consists of PMs and transverse windings for each phase, as shown in Figure 4 [31]. As a result, FSPMLEMs have superior reliability due to their simple and rugged mover structure, and they are featured with high force density, high efficiency but high force ripple [32,33].…”
Section: Different Flux Type Permanent Magnet Lemsmentioning
confidence: 99%
See 1 more Smart Citation